Projeto desenvolvimentista, propriedade da terra e produção agrícola no Norte do RS (1930-1945) - Comiran, Vitória (2021)
The rural world has always been important for the constitution of the history of Brazil. In different periods it represented how the country's political and economic situation was structured. Thus, knowing and interpreting the organization of the rural world in a specific space and temporality speaks volumes about regional and national history, state policies, socioeconomic and political circumstances of its protagonists. In this sense, this work seeks to discuss the repercussions of the socioeconomic policy of the Vargas government (1930-1945), called developmentalist, in the rural world of northern Rio Grande do Sul. The research was developed through the reading of documents from the Land Colonization of Passo Fundo, such as: mail sent and received; letters sent and received; colonial debt collection guides; application forms; title records; records of batch concessions; application protocols and expense documents. The action of the referred Commission is analyzed, mainly, to what is alluded to the property of the land and the agrarian production. These issues of importance to the rural world concern the concrete experience of the developmental socio-economic project of the Vargas government. The study discusses the structuring of land ownership in the north of Rio Grande do Sul in the 1930s and 1930s, identifying the practices and their actors, the possibilities and the limits of the developmental project in relation to agricultural production and its variables. In order to carry out the research, we first seek to contextualize the Vargas Era period, the socioeconomic project and its bases: nationalism; industrialization; pro-growth interventionism. In addition, the rural world in the north of the state is discussed, as well as the modernization actions introduced since 1930 by the Vargas government and which were put into practice by the Passo Fundo’s Land and Colonization Commission. Its performance th us reflects the process of occupation, appropriation of new land and the capitalization of land ownership in the north of RS.